The Shelleys and the Brownings : textual re-imaginings and the question of influence - Suzuki, Rieko (English Association monographs. English at the interface, 2022)
This book is about the intertextual relationships between the works of the Shelleys and the Brownings. While a lot of research has been done on the relationship between Percy Bysshe Shelley and Robert Browning, virtually nothing has been said about the links between Mary Shelley and Robert Browning, and very little on the connections between the Shelleys and Elizabeth Barrett Browning. Rieko Suzuki seeks to address this blind spot by focusing on three areas in particular: firstly, the way that Browning's later poems reflect back on and re-engage with Shelley's work; secondly, Mary Shelley's influence on Browning's early poems; and thirdly, Shelley's presence in and influence on Elizabeth Barrett Browning's writing. In mapping out the various ways in which texts relate to other texts, the book also identifies a number of important thematic threads that run throughout the work of all four writers. These include theories of history and historical consciousness, providing a further dime...